Potential of wind energy in Medina, Saudi Arabia based on Weibull distribution parameters. Issue 6 (December 2021) - AlQdah, Khaled S; Alahmdi, Raed; Alansari, Abdulrahman; Almoghamisi, Abdulrahman; Abualkhair, Mohanad; Awais, Muhammad
This study aims to assess the potential of wind energy in Medina by using Weibull probability distribution to provide an insight concerning the energy production from the selected wind turbine Aventa AV-7. Scale factors c and shape k of Weibull distribution, were determined for wind speed frequency. Significant findings included a wind speed recurrence of 2.9 m/s with a probability of 30% approximately. The average c and k were found to be 3.467 and 2.923 m/s, respectively. The estimated average k is relatively high, which indicates that the spread in wind speeds is small. Aventa AV-7 turbine was chosen to test the power generation of wind in Medina. It was found that this wind turbine can generate 8648 kWh/year in the Medina region, which is only 15.2% of the maximum power production. This turbine is expected to generate the maximum possible power output at a wind speed of 7 m/s.